Improving Students’ Skimming and Scanning in Reading Skill by Applying Metacognitive Strategy - Siti Mariam (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2016)
Reading is one of the main four language skills that a learner needs to master in order to ensure success in learning English. To facilitate students in comprehending a text, the effective strategies should be used. One of the strategies is Meta-cognitive strategies. The objectives of the research are to identify students’ responses during learned process by using Meta-cognitive strategies and to investigate how high students’ improvement of skimming and scanning reading skill after learned by using Meta-cognitive strategies in recount text. Meta-cognitive strategies improve students to reflect on thought processes and to plan, monitor, and evaluate aspects of their learning. The participants were third semester of English department students of Islamic Education and Teacher Training Faculty of Walisongo State Islamic University.The reserch design was Classroom Action Research with 1 preliminary cycle and 2 cycles. This research was conducted from March, 2th 2015 until March, 21th 2015. Data collection technique was tests. Observations were done in each cycle. Tests form was given the students, they should answer 20 questions of multiple choice test. Then, the data were analyzed using mean (descriptive statistics) to find out the improvements. Meta-cognitive strategies were applied in the teaching learning process by giving plan (giving task for students), monitoring, evaluating, and problem solving to the students. After collecting the data, the result showed the improvements of the students. Students’ average score in pre cycle test was 60. In the first cycle, the average score increased became 70. This score hadn’t met the minimum standard score yet 75. Therefore, second cycle was conducted. Students’ average score increased became 82.16. Students’ engagements also increased since the first cycle. Consequently, the objectives were reached. Based on the result, it could be concluded that Meta-cognitive strategy can improve the students’ skimming reading comprehension of recount text